Research of Biometric Key Generation Based on Fingerprint Bit-strings (Journal of Fiber Bioengineering and Informatics, 2015)
Biometric key technology is the organic combination of biometric encryption technology and traditional\rcryptography. Biometric key can directly encrypt data or encrypt key, with the character of portable use\rand not easily being stolen, forgotten and broken. This article provides an algorithm for generating key\rbased on the fingerprint feature bit-strings, extracting \fngerprint feature information with bit-strings\rform as first step, generating key by the combination of this feature information and BCH error correcting\rcode secondly. Experiments show that the algorithm can generate stable key of encryption on the premise\rof protecting the user's \fngerprint information. It can further improve the security strength and reach\rtwo-factors protection if the biometric key is stored in the smart card, which has certain practical value.
Keywords: Fingerprint; Fuzzy Schemes; Bit-strings; Error-correcting Code; Biometric Encryption